Frontal fibrosing alopecia: a disease that remains enigmatic - Lis-Święty, Anna; Brzeźińska-Wcisło, Ligia (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2020)
Frontal fibrosing alopecia (FFA) is recognized to represent a generalized process of inflammatory scarring alopecia. Apart from the classic form affecting the frontal hairline, there are a range of disease manifestations involving loss of eyebrows and of eyelashes, loss of peripheral body hair, ﬁbrosing alopecia in a pattern distribution, facial and extrafacial skin, mucous membrane, and nail involvement. Classic linear, diffuse “zigzag”, pseudo “fringe sign”, androgenetic alopecia-like, cockade-like, ophiasis-like and incomplete patterns are distinguished. The aetiology of FFA remains obscure, but a number of pathogenetic hypotheses and treatments to halt disease progression have been proposed.